THE COMFORT CONDITIONS ASSESSMENT IN TRAINING ENVIRONMENTS BUILT USING MIXED CONSTRUCTION TYPES AT CENTRO DE GESTIÓN Y DESARROLLO SOSTENIBLE DEL SURCOLOMBIANO: CENTRO DE GESTIÓN Y DESARROLLO SOSTENIBLE DEL SURCOLOMBIANO DE LA SEDE YAMBORÓ PITALITO – HUILA - GUEVARA SILVA, ALBA LORENA GUEVARA SILVA
The objective of this research was to evaluate the environmental conditions: visual, thermal, and auditory, of the three types of training environment designs existing in the Centro de Gestión y Desarrollo Sostenible del Surcolombiano SENA, Regional Huila, to validate compliance with the Colombian Technical Standard NTC 4595, Civil Engineering and Architecture Planning and Design of School Facilities and Environments, of the Ministry of Education. Using quantitative research, a daily record was made from 9:00 am to 4:00 pm. From this record, the information was collected and the data obtained were tabulated, taking into account the variables luminosity, temperature / relative humidity, and sound levels, to finally conclude that the Type A1, B2, and C3 training environments do not meet the conditions of visual, thermal and auditory comfort established by the standard, either because they exceed or do not reach the parameters studied.